In-situ synthesis of porous metal fluoride@carbon composite via simultaneous etching/fluorination enabled superior Li storage performance. (1st December 2022) - Du, Kang; Tao, Runming; Guo, Chi; Li, Haifeng; Liu, Xiaolang; Guo, Pingmei; Wang, Deyu; Liang, Jiyuan; Li, Jianlin; Dai, Sheng; Sun, Xiao-Guang
Abstract: Transition metal fluorides as Li-free conversion-type cathode materials have high theoretical specific capacities, however, their preparation strategy, sluggish electrochemical kinetic and poor cyclability have impeded their wide adoption in lithium-ion batteries. Herein, a facile in-situ synthesis of porous metal-fluoride-carbon composites is accomplished via simultaneous polytetrafluorethylene-based hard template etching and metal fluorination. This not only facilitates fast electron transfer and lithium-ion diffusion kinetics, but also buffers severe volume fluctuation during lithiation/delithation and enables the formation of a uniform and thin Li2 CO3 /LiF-rich cathode-electrolyte interphase. As a proof of concept, the as-prepared porous FeF3 @C (p-FeF3 @C) indeed exhibits a high specific capacity of 230 mAh g −1 at 0.1 C together with an excellent capacity retention of 92.5% at 1 C for 200-cycles. Moreover, the practicality of the strategy is demonstrated by the superb electrochemical performance of the full-cells coupled with pre-lithiated graphite anodes. Therefore, the proposed novel synthetic strategy will enlighten the future design of high-performance metal-fluoride-carbon composites with porous structure for energy storage applications. Graphical Abstract: Porous metal-fluoride-carbon composites is synthesized via simultaneous polytetrafluorethylene-based hard template etching and metal fluorination. They can not only facilitate fast electron transfer and lithium-ion diffusion kinetics but also buffer severe volume fluctuation during lithiation/delithation, exhibiting a high specific capacity of 230 mAh g −1 at 0.1 C and a high capacity retention of 92.5% at 1 C for 200-cycles. ga1 Highlights: Porous iron-fluoride-carbon composites (p-FeF3 @C) is synthesized via simultaneous polytetrafluorethylene-based hard template etching and metal fluorination. A uniform and thin Li2 CO3 /LiF-rich cathode-electrolyte interphase can be formed on the p-FeF3 @C. p-FeF3 @C exhibits a high specific capacity of 230 mAh g −1 at 0.1 C and a high capacity retention of 92.5% at 1 C for 200-cycles. Full-cell of p-FeF3 @C with pre-lithiated graphite anodes exhibits superb electrochemical performance.